Towards a manipulation of memory by science?: a contextualized analysis of the films Final Cut and Eternal Sunshine of the Spotless Mind - Matos Trindade, Carlos Alberto (Technium Social Sciences Journal, 2021)
In this article, after a general introduction about a brain prosthesis project - a substitute for the hippocampus -, started in 2003 by a team of neuroscientists from the University of Southern California, and experiments started between 2007 and 2009 by scientists of various nationalities, we present in more detail some of the main results of the latter, published in scientific articles, which allow us to predict some potential risks in the future, and pose ethical problems, for worthy intentions that scientists may have. Following this, we discuss films Final Cut (2004) by Omar Naim and Eternal Sunshine of the Spotless Mind (2004), directed by Michel Gondry, which present multiple points of contact with the aforementioned scientific projects, anticipating some of the foreseeable dangers, and allow us to discuss the future possibility of a manipulation of memory (and of oblivion), through science. Although they are fiction films, much of what is shown in both is compatible (except for some aspects) with real neuroscience research projects that are currently underway.